Pedal cum solar powered paddy thresher for small farms - J, SRIKANTHNAIK; SHARMA, P K; KUSHWAHA, H L (The Indian Journal of Agricultural Sciences, 2021)
The performance of pedal operated paddy thresher was evaluated in the field. During threshing operation the optimum speed of threshing drum 290-310 rpm was achieved by 21 strokes. The paddy was threshed at a moisture content of 18.45%. The threshing efficiency of the thresher was found up to 99%. The optimum paddy holding capacity achieved was 0.5 kg, 1 kg and 0.75 kg. The optimum foot pedal size was 14.35 cm. The optimum threshing cylinder height was 101.25 cm. Threshing efficiency in solar mode was found as 99.58-98.67% compared to 98.54-97.01% for pedal. The threshing rate in solar mode was achieved as 231.67 kg/h as compared to 66.63 kg/h in pedal mode. Hence, solar mode threshing rate is 3.47 times more than pedal mode. This thresher will be very useful for small poor farmers in rural areas where there is no electricity or its supply is erratic. Due to its small weight it will also be very useful for farmers in hilly regions due to its easy transport from one place to another.